Analysis on cause of erosion of guide vane of high‐head Francis turbine in sandy river - Haiqi Wang; Jiayang Pang; Xiaobing Liu; Ziyao Zhou; Yuanyuan Gang; Zhenming Lai; Jianming Wang; Bo Qin (Energy Science & Engineering)
Abstract The Kizilsu River Basin in China is located in the desert Gobi area with high sediment content and high hardness. After 4798h operation, the maintenance of a high‐head Francis turbine in this basin found that the guide vane was seriously worn, and even most of the top and lower skirts of the front of the guide vane were worn off. In this study, the k‐ε turbulence model, ZGB cavitation model and sediment erosion prediction model were used to simulate the solid‐liquid two‐phase flow and cavitation of guide vane. The research results show that the guide vane of a high‐head Francis turbine in a sandy river has a high sediment velocity and serious surface erosion, with the maximum erosion rate of 1.0 × 10−6 kg/(m2·s), while the area near the skirt of the guide vane is a low‐pressure area lower than the saturated steam pressure, and cavitation is very easy to occur, with the maximum vapor volume fraction of 0.9. Serious cavitation erosion occurs near the skirt of the guide vane, and the combined effect of sand erosion and cavitation erosion on the surface of the skirt of the guide vane aggravates the damage of the skirt structure. The research results provide a technical basis for the antiabrasion design of the guide mechanism of the high‐head Francis turbine and the operation and maintenance of the hydropower station in the sandy river.